Insulin- like Growth Factor-Binding Protein Action in Bone Tissue: A Key Role for Pregnancy- Associated Plasma Protein-A - Beattie, James; Al-Khafaji, Hasanain; Noer, Pernille R.; Alkharobi, Hanaa Esa; Alhodhodi, Aishah; Meade, Josephine; El-Gendy, Reem; Oxvig, Claus (Frontiers in Endocrinology, 2018)
The IGF axis is required for the differentiation, development and maintenance of bone tissue. Accordingly, dysregulation of this axis is associated with various skeletal pathologies including growth abnormalities and compromised bone structure. It is becoming increasingly apparent that the action of the IGF axis must be viewed holistically taking into account not just the actions of the growth factors and receptors, but also the influence of soluble high affinity IGF binding proteins There is a recognition that IGFBPs exert IGF-dependent and IGF-independent effects in bone and other tissues and that an understanding of the mechanisms of action of IGFBPs and their regulation in the pericellular environment impact critically on tissue physiology. In this respect, a group of IGFBP proteinases (which may be considered as ancillary members of the IGF axis) play a crucial role in regulating IGFBP function. This theory suggests that cleavage of IGFBPs by specific proteinases into non-IGF binding fragments regulates the partition of IGFs between IGFBPs and cell surface IGF receptors. In this report, we review the importance of IGFBP function in bone tissue with special emphasis on the role of PAPP-A. We examine the function of PAPP-A primarily as an IGFBP-4 proteinase (concentrating on IGFBP-4), and present evidence that PAPP-A induced cleavage of IGFBP-4 is a key regulatory point in bone tissue metabolism. We also highlight some recent findings with regard to IGFBP-2 and IGFBP-5 (also PAPP-A substrates) action in bone tissue and briefly discuss the actions of the other three IGFBPs (-1, -3 and -6) in bone. Our main focus will be in bone tissue but we allude to IGFBP activity in other cells and tissues when appropriate.